2012
DOI: 10.1007/s10903-012-9645-z
|View full text |Cite
|
Sign up to set email alerts
|

Resources and Interest Among Faith Based Organizations for Influenza Vaccination Programs

Abstract: In the United States, annual influenza vaccination rates are suboptimal and are well below the national health objectives. Project VIVA mobilized community members and organizations to implement an influenza vaccination program in Harlem by administering vaccines in “non-traditional” venues, such as community-based organizations, pharmacies, and faith-based organizations (FBOs). FBOs have been recognized as important venues for health promotion initiatives within medically underserved communities. However, dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Our findings are consistent with a number of other studies that found high levels of interest in offering health programs among FBOs [26,27]. Our finding that FBOs score highly on measures of organizational readiness suggests that they may be ready organizational partners for adoption of health interventions.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with a number of other studies that found high levels of interest in offering health programs among FBOs [26,27]. Our finding that FBOs score highly on measures of organizational readiness suggests that they may be ready organizational partners for adoption of health interventions.…”
Section: Discussionsupporting
confidence: 92%
“…Given the urgent need for improved COVID-19 transmission prevention behaviors, and targeted public health campaigns for high-risk populations and their caretakers, we recommend building on lessons learned from successful prevention strategies and policies that can be applied to the conservative voting base. For example, leveraging community-based partnerships with conservative community organizations and using incentives such as monetary compensation to improve prevention adherence [65]. Increasing access to services and benefits (e.g., paid sick leave) that allow for individuals to engage in preventative health behaviors is also paramount [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Community engagement by the pharmacy within the Immunization Neighborhood is also of paramount importance, and in fact has been displayed as an untapped resource with needs that the vaccination 'team' (especially those with university affiliation) are well-positioned to assist with. 94 Of note, this approach assimilates patients and families representing those with pro-and anti-vaccine viewpoints, as well as those who are vaccine hesitant. Strategically, their proposed 'paths' in this concept are less divergent than one would initially think.…”
Section: Proposed Multifaceted Immunization Conceptmentioning
confidence: 99%